2018
DOI: 10.1111/ijd.14304
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of skin diseases among hospitals in the public healthcare system of a developing country

Abstract: Background Skin diseases in the population are universal, common, and can cause significant economic burden. The impact of skin diseases in the national public healthcare system is complex and poorly studied. This study analyzes the prevalence of skin diseases in a hospital setting within the National Public Health System of Mexico and describes the main associated characteristics. Methods Information was obtained from the 2015 hospital discharge database of the public healthcare system of Mexico. Pathologies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 18 publications
1
13
0
4
Order By: Relevance
“…Gender differences in the incidence, prevalence and prognosis of skin diseases, as well as cultural aspects and disease coping strategies may explain the higher admissions of males [23–25]. Median length of stay was longer in our sample than in the Mexican study, and the proportion of hospital deaths higher [2]. These differences could be explained because the Spanish population has one of the highest average ages and life expectancies in the world, and also by the fact that the public health system in Mexico could provide different services to the Spanish one [26, 27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender differences in the incidence, prevalence and prognosis of skin diseases, as well as cultural aspects and disease coping strategies may explain the higher admissions of males [23–25]. Median length of stay was longer in our sample than in the Mexican study, and the proportion of hospital deaths higher [2]. These differences could be explained because the Spanish population has one of the highest average ages and life expectancies in the world, and also by the fact that the public health system in Mexico could provide different services to the Spanish one [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing particular diseases, skin infections, specifically cellulitis and acute lymphangitis, are the more prevalent cause of dermatological admissions, as Soria Orozco et al. observed in their investigation [2]. Cutaneous infections are relatively common visits at the emergency departments, and almost 30 % of these patients are admitted to hospitals [28].…”
Section: Discussionmentioning
confidence: 99%
“…4 A large hospital network database study from Mexico, a study in a pediatric dermatologic clinic in Thailand, a study in Thai elderly patients showed infections as 32.1%, 21.9, and 21.9% of all skin diseases, respectively. 5,6,7 The most common skin disease in a questionnaire survey were warts (41.3%), followed by acne (19.2%) and contact dermatitis (15.0%). 8 The global burden of disease study showed 0.4% of burden for dermatitis (atopic, contact, and seborrheic dermatitis), 0.3% for acne vulgaris, 0.2% for psoriasis, 0.2% for urticaria, 0.1% for pyoderma and cellulitis.…”
Section: Discussionmentioning
confidence: 99%
“…Wir konnten nur eine aktuelle landesweite Erhebung finden, welche die Hauptursachen für dermatologisch bedingte Krankenhauseinweisungen und deren Besonderheiten untersuchte. Allerdings bezog sich diese nur auf den begrenzten Zeitraum von einem Jahr im nationalen öffentlichen Gesundheitssystem von Mexiko [2]. Mit 57 Jahren war das mediane Alter in unserer Stichprobe 4,5 Jahre höher als in der mexikanischen Studie berichtet, das mittlere Alter war 10 Jahre höher.…”
Section: Diskussionunclassified
“…Betrachtet man die einzelnen Erkrankungen, so sind Infektionen der Haut, insbesondere Phlegmone und akute Lymphangitis, die häufigste Ursache für eine stationäre dermatologische Aufnahme, wie Soria Orozco et al. in ihrer Untersuchung feststellten [2]. Hautinfektionen sind relativ häufig Anlass für Visiten in den Notaufnahmen, und fast 30 % dieser Patienten werden stationär aufgenommen [28].…”
Section: Diskussionunclassified